Glutamate cysteine ligase catalytic subunit promoter polymorphisms and associations with type 1 diabetes age-at-onset and GAD65 autoantibody levels - Bekris, L M; Shephard, C; Janer, M; Graham, J; McNeney, B; Shin, J; Zarghami, M; Griffith, W; Farin, F; Kavanagh, T J; Lernmark, A (Experimental and clinical endocrinology & diabetes, 2007)
The purpose of this study was to test the hypothesis that glutamate cysteine ligase catalytic subunit (GCLC) promoter polymorphisms are susceptibility factors for type 1 diabetes (T1D), T1D age-at-onset and T1D autoantibodies. T1D patients and control subjects from the Swedish Childhood Diabetes Registry and the Swedish Diabetes Incidence Study registry were genotyped for two GCLC promoter polymorphisms; the GCLC -129 C to T single nucleotide polymorphism (GCLC -129 SNP) and the GCLC GAG trinucleotide repeat polymorphism (GCLC TNR). Glutamate decarboxylase antibody (GAD65Ab) positive T1D patients with the GCLC -129 SNP C/T genotype have increased GAD65Ab levels (p-value, <0.05) compared to the GCLC -129 SNP C/C genotype. T1D patients with an age-at-onset of 14-35 years who possess the GCLC -129 SNP T/T genotype have a higher GAD65Ab index than T1D patients with the GCLC -129 SNP C/C genotype (p-value <0.05). In addition, T1D patients with an age-at-onset of 14-35 years possess the GCLC TNR 7/8 genotype at a lower frequency than the control subjects (OR, 0.33, 95% CI, 0.13-0.82). The GCLC -129 SNP and GCLC TNR appear to be in linkage disequilibrium (p-value<0.0001). These results suggest that GCLC promoter polymorphisms may influence GAD65Ab levels and may influence the age at which T1D is diagnosed.